An improved negative zero vibration anti-swing control strategy for grab ship unloader based on elastic wire rope model - Cao Xiaohua (EDP Sciences, 2021)
A dynamic model of swing system of bridge-type ship unloader is established by considering the elastic factor of wire rope in this paper. Based on this model, an improved Negative Zero Vibration (NZV) shaper with optimal control parameters of variable rope length system is proposed to restrain the swing of grab. Then the control effects, influence of elasticity factor and parameter sensitivities are analyzed based on numerical simulation. The results show that the proposed control strategy can reduce the working cycle time of the grab ship unloader about 11% when considering the elastic factor of the wire rope, and the grab's maximum residual swing angle decreases by 67% when discharging at full load, and decreases by 79% when taking the cargos at empty load. This implies that the improved NZV control method provides better swing angle control performance and shorter operation time compared with the Zero Vibration (ZV) and Zero Vibration and Derivative (ZVD) methods. Moreover, elastic rope model can improve the swing angle control effect of grab based on the proposed control strategy compared with rigid rope model. The parameter sensitivity analysis displays that the grab's maximum residual swing angle by using the improved NZV method is sensitive to the change of the grab's center of gravity, and this angle is more sensitive to the wire rope diameter deviation compared with the elastic modulus deviation.